Voiceless but empowered farmers in corporate supply chains: contradictory imagery and instrumental approach to empowerment - McCarthy, Lucy; Touboulic, Anne; Matthews, Lee (SAGE, 2018)
There have been calls for a shift of focus towards the political and power-laden aspects of transitioning towards socially equitable global supply chains. This paper offers an empirically grounded response to these calls from a critical realist stance in the context of global food supply chains. We examine how an imaginary for sustainable farming structured around an instrumental construction of empowerment limits what is viewed as permissible, desirable and possible in global food supply chains. We adopt a multimodal Critical Discourse Analysis (CDA) to examine the sustainable farming imaginary for smallholder farmers constructed by one large organization, Unilever, in a series of videos produced and disseminated on YouTube. We expose the underlying mechanisms of power and marginalization at work within the sustainability imaginary and show how “empowerment” has the potential to create of new dependencies for these farmers. We recontextualize the representations to show that while the imaginary may be commercially feasible, it is less achievable in terms of empowering smallholder farmers.